Duolingo Application as a Vocabulary Learning Tool Used by Students of Tadris Bahasa Inggris in STAIN Madina - Batubara, Muhammad Hasyimsyah (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
This research aims to see the effectiveness of Duolingo as a vocabulary learning tool in building the vocabulary skills of English Language Education students at STAIN Madina semester 1. This study also explores how this application motivates students in independent learning and identifies its advantages and disadvantages. Quantitative methods were used involving 22 students as samples. Data was gathered via pre-tests and post-tests to measure the increase in vocabulary skills, as well as questionnaires to determine students' perceptions of using Duolingo. The findings showed an obvious increase in students' vocabulary skills after employing Duolingo, with an average pre-test of 62.4 and a post-test of 78.1. The paired t-test represents a p-value of 0.000 (p <0.05), which means that using Duolingo effectively improves vocabulary skills. In addition, 80% of students reported increased motivation in learning vocabulary through this application. However, some students identified limitations in the application content that focuses more on everyday language. This study concludes that Duolingo is an effective learning tool and can motivate students to learn vocabulary independently according to academic needs.